Sistem Pendukung Keputusan untuk Penentuan Klasifikasi Status Hotel - Asrul, Billy Eden William; Zuhriyah, Sitti; Anatasya, A. Edeth Fuari (Prosiding SISFOTEK, 2024)
The Hotel industry is a key component of the tourism sector that is required to obtain business certification. This certification determines the star classification of a hotel. The determination of 1, 2, 3, 4, and 5-star classifications for hotels, particularly in the city of Makassar, involves the Tourism Business Certification Agency (LSUP) as the auditing body, the Makassar City Tourism Office as the regulatory body responsible for supervision and guidance, and the industry as the auditee. The conventional and manual processes for determining star ratings reduce the effectiveness and efficiency of audit implementation, as well as hinder the supervision of business certification by the Makassar City government.